2021
DOI: 10.1002/cam4.4463
|View full text |Cite
|
Sign up to set email alerts
|

Age‐specific clinicopathological characteristics and prognostic analysis of neuroendocrine carcinomas of the gallbladder

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
(84 reference statements)
2
8
0
Order By: Relevance
“…NECs accounted for the largest number of neoplasms (16/36), with 4 cases being LCNECs and 12 cases being SCNECs, consistent with previous reports that NECs are predominantly SCNECs (17). The expression of markers did not signi cantly differ among the three locations of neoplastic cells and did not have an impact on patient survival.…”
Section: Discussionsupporting
confidence: 87%
“…NECs accounted for the largest number of neoplasms (16/36), with 4 cases being LCNECs and 12 cases being SCNECs, consistent with previous reports that NECs are predominantly SCNECs (17). The expression of markers did not signi cantly differ among the three locations of neoplastic cells and did not have an impact on patient survival.…”
Section: Discussionsupporting
confidence: 87%
“…Three studies, involving 10, 15, and 28 patients with gallbladder NEN, reported a worse prognosis in patients with gallbladder NEN than those with adenocarcinoma. 10,11,29 In another study of 21 patients, the outcomes were similar. 3 However, another study including 754 patients with gallbladder NEN revealed that the prognosis of gallbladder NEN was better than that of adenocarcinoma.…”
Section: Discussionmentioning
confidence: 87%
“…However, different studies have arrived at different conclusions regarding the prognosis of gallbladder NEN. Three studies, involving 10, 15, and 28 patients with gallbladder NEN, reported a worse prognosis in patients with gallbladder NEN than those with adenocarcinoma 10,11,29 . In another study of 21 patients, the outcomes were similar 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On re‐evaluation, 31 (21.1%) patients were upstaged to either locally advanced or metastatic stages. NEC and MiNEN are aggressive diseases with prognosis worse than adenocarcinoma 2,5,6 . Fifty‐two (35.4%) patients in our series could not receive any treatment due to poor performance status, intractable jaundice, or very advanced nature of the disease.…”
Section: Discussionmentioning
confidence: 85%